Could α-Synuclein Modulation of Insulin and Dopamine Identify a Novel Link Between Parkinson’s Disease and Diabetes as Well as Potential Therapies? - Vidal-Martinez, Guadalupe; Yang, Barbara; Vargas-Medrano, Javier; Perez, Ruth G. (Frontiers in Molecular Neuroscience, 2018)
Characterizing the normal function(s) of the protein α-Synuclein (aSyn) has the potential to illuminate links between Parkinson’s disease (PD) and diabetes and also point the way toward new therapies for these disorders. Here we provide a perspective for consideration based on our discovery that aSyn normally acts to inhibit insulin secretion from pancreatic β-cells by interacting with the Kir6.2 subunit of the ATP-sensitive potassium channel (K-ATP). It is also known that K-ATP channels act to inhibit brain dopamine secretion, and we have also shown that aSyn is a normal inhibitor of dopamine synthesis. The finding that aSyn modulates Kir6.2 and other proteins involved in dopamine and insulin secretion, suggest that aSyn interacting proteins may be negatively impacted when aSyn aggregates inside cells. Furthermore, identifying therapies for PD that can counteract dysfunctions found in diabetes, would be highly beneficial. One such compound may be the multiple sclerosis drug, FTY720, which like aSyn can stimulate the activity of the catalytic subunit of protein phosphatase 2A (PP2Ac) as well as insulin secretion. In aging aSyn transgenic mice given long term oral FTY720, the mice had reduced aSyn pathology and increased levels of the protective molecule, brain derived neurotrophic factor (BDNF) [1]. In collaboration with medicinal chemists, we made two non-immunosuppressive FTY720s that also enhance PP2Ac activity and BDNF expression [2; 3; 4]. FTY720 and our novel FTY720-based-derivatives, may thus have therapeutic potential for both diabetes and PD.